A autonomia da vontade nos contratos internacionais nos países do Mercosul - Nicareta, Flavia Carina Tulio (2012)
The aim of this work is to investigate the will´s autonomy that take place in worldwide contracts at Mercosul. The study has been focused in demonstrating that will´s autonomy enables parties to choose where to be in a contract, providing thus an improvement in the sense that global trends when it comes to acceptance happens in using this outset. It has been verified worldwide contracts, its preparation and private global law. It has also been used the will´s autonomy issue and its contexts. The aim has also been on demonstrating Mercosul sense and how has its development going forward. Finally, the main objective is to investigate how such outset is dealt with when it comes to global contracts signed in Mercosul environment